Which Kind of Land Reform for Ethiopia: The Debate Preceding the 1975 Land Proclamation - Abebe, Mengistu (Ethiopian Journal of Social Sciences, 2018)
Sustained agricultural development depends on the proper management of the land and the people, and their relationships-i.e. the system of land tenure. The feudal system of Ethiopia was, however, believed to be a bottleneck for the utilization of the country’s agricultural potential. Then, the students and the progressive intelligentsia played the vanguard role in the political agitation for land reform for more than a decade. The imperial government was unable to meet the demands of the popular movement that ultimately brought the regime to its demise. On September 2, 1974 the Provisional Military Administrative Council (PMAC) commonly called ‘Derg’ controlled the government. Then, the issue of land reform became the subject of much discussion and controversy within the PMAC, student groups and radical intelligentsia and the public at large. The debate was conducted on two different levels, formally in the government institutions and in the official newspapers, and informally in the underground publications and in public gatherings. It took about six months of discussion and elaboration for the PMAC until its radical wing finally proclaimed the March 1975 land reform. The foregoing debate revealed the degree of polarization between the reformists and the revolutionists. The major questions in the struggle between the two poles were centered around the objective of the land reform, the issue of land ownership and of ceilings, and the method of its implementation.